Tracking and stress-testing U.S. household leverage - Andreas Fuster; Benedict Guttman-Kenney; Andrew Haughwout (Federal Reserve Bank of New York, 2016)
Borrowers' housing equity is an important component of their wealth and a critical determinant of their vulnerability to shocks. In this paper, we create a unique data set that allows us to provide a comprehensive look at the ratio of housing debt to housing values - what we refer to as household leverage - at the micro level. An advantage of our data is that we are able to study the evolution of household leverage over time and across locations in the United States. We find that leverage was at a very low point just prior to the large declines in house prices that began in 2006, but it rose very quickly thereafter, despite reductions in housing debt. As of late 2015, leverage statistics are approaching their pre-crisis levels, as house prices have risen over 30 percent nationally since 2012. We use our borrower-level leverage measures and another unique feature of our data - updated borrower credit scores - to conduct "stress tests": projecting leverage and defaults under various adverse house price scenarios. We find that while the riskiness of the household sector has declined significantly since 2012, it remains vulnerable to very severe declines in house prices.
Keywords: D14; E27; G21; 330; mortgages; leverage; stress testing